Review on Helicobacter pylori associated Diseases - SHahrazad H. Muhi; Farah Badri Abed; Nada H. Bedair; Saba R. Jaafar; Sahar M. Ibrahim; Dunya Abdullah Mohammed; Omar A. Mahmoud; Ruaa H. Ali; Mohammed Ayad Hameed; Luma Mahmood Edan (Baghdad Journal of Biochemistry and Applied Biological Sciences)
One of the most common and enduring bacterial infections globally, Helicobacter pylori (H. pylori) infects almost half of the world’s population. The bacterium is described as a spiral microaerophilic gram-negative bacterium; it is commonly found in the stomach and can cause several categories of gastrointestinal conditions, such as gastritis, peptic ulcers, and in some circumstances, stomach cancer. There is also a growing knowledge that chronic H. pylori infection may be associated with an increased danger of extra-gastric disease that includes host iron deficiency anemia, and cardiovascular, autoimmune, metabolic, neurological, and dermatological diseases. In this article, we examined the virulence factors of H. pylori and its correlation to gastrointestinal diseases, as well as the bacterium’s potential involvement in extra-gastric diseases such as iron and vitamin B12 deficiency, in addition to neurological, cardiovascular, inflammatory bowel, and diabetes mellitus disorders.